The return of the kinga (saltwater crocodile): Population 'bust then boom' shapes shifting baselines in Indigenous biocultural knowledge in northern Australia. (January 2023) - Ligtermoet, Emma; Gumurdul, Julie Narndal; Nayinggul, Connie; Baker, Richard
Abstract: The saltwater crocodile ( Crocodylus porosus ) can be regarded as a cultural keystone species for many Indigenous societies around the world, including for many Aboriginal clans in northern Australia. Here the regional population of Crocodylus porosus suffered a decline, almost to extinction, with unregulated commercial hunting between the 1940s to the early 1970s. Following protected status, saltwater crocodile populations made a rapid recovery. This research documents the perceptions and experiences of this rapid (within living memory) 'bust then boom' saltwater crocodile population change, among a regional group of Indigenous Australians (comprising several clans) from the Alligator Rivers Region of western Arnhem Land and Kakadu National Park in the Northern Territory. Using semi-structured interviews, archival work and on-Country (place-based) learning, significant influences on the continuity of Aboriginal people's contemporary engagement with freshwater Country were identified. In particular, the loss of access to freshwater customary harvesting sites and to key harvested species, and as a driver of adaptive changes in harvesting methods and consumption preferences for saltwater crocodile meat and eggs. Importantly, the experiential losses from restricted access to waterbodies were found to have significant impact on opportunities for inter-generational knowledge transmission, according with more recent applications of the Shifting Baseline Syndrome to Indigenous Ecological Knowledge. Findings demonstrate the need for monitoring and management programs of cultural keystone species, like the saltwater crocodile, to include Indigenous-led biocultural knowledge programs as a means of supporting local and Indigenous Knowledge systems. This is particularly critical in cross-cultural, First Nations, and joint-management contexts.